2017
DOI: 10.1001/jama.2017.17426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Indwelling Pleural Catheter vs Talc Pleurodesis on Hospitalization Days in Patients With Malignant Pleural Effusion

Abstract: anzctr.org.au Identifier: ACTRN12611000567921.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
230
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(254 citation statements)
references
References 35 publications
14
230
1
9
Order By: Relevance
“…IPC use is increasing with the increasing number of high quality clinical studies and randomized trials providing evidence of efficacious use [1,2], in both malignant and non-malignant disease [4,10]. While it is now established that in MPE, IPC and talc pleurodesis have similar beneficial effects on important patient outcomes such as breathlessness [1], the majority of studies have focused on short term, hospital focused outcomes such as hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPC use is increasing with the increasing number of high quality clinical studies and randomized trials providing evidence of efficacious use [1,2], in both malignant and non-malignant disease [4,10]. While it is now established that in MPE, IPC and talc pleurodesis have similar beneficial effects on important patient outcomes such as breathlessness [1], the majority of studies have focused on short term, hospital focused outcomes such as hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Since published randomized data demonstrated similar symptomatic improvement using IPC or talc pleurodesis in MPE [1], standard practice in the Oxford Pleural Unit is to offer patients a choice between talc pleurodesis and IPC insertion. Two randomized trials demonstrated that IPCs avoid hospital stay in MPE, and are therefore an increasingly attractive option for patients wishing to avoid hospitalization [1,2]. However, there is a lack of evidence about the overall impact of IPCs on patients and hospital visits beyond the initial insertion procedure done as a day case procedure, and usual scheduled outpatient visits.…”
Section: Introductionmentioning
confidence: 99%
“…Ein Vergleich einer Pleurodese via IPC gegenüber einer Thoraxdrainage ist aktuell Gegenstand einer klinischen Studie [3]. Die symptomatische Besserung, die durch einen IPC (ohne Pleurodese) erreicht werden kann, scheint hingegen vergleichbar mit einer Pleurodese via Thoraxdrainge [2,4]. Somit ist bei der Entscheidung IPC, IPC + Pleurodese oder Thoraxdrainage + Pleurodese das Therapieziel unter Berücksichtigung des Patientenwunsches und des Patientenmanagements genau zu definieren und das entsprechend geeignete Verfahren zu wählen.…”
Section: Transfer In Die Praxis Von Dr Stefanie Keymel (Düsseldorf)unclassified
“…Das durchschnittliche Alter der Patienten beträgt in dieser und anderen Studien, z.B. AMPLE [4], >60 Jahre. Fortgeschrittenes Alter sowie Begleiterkrankungen begünstigen eher ein nicht operatives Management.…”
Section: Transfer In Die Praxis Von Dr Stefanie Keymel (Düsseldorf)unclassified
“…The latter has the advantage of being used to either chronically drain the pleural space, or to facilitate chemical or autopleurodesis [3], and several studies have confirmed that the improvement in QoL and other patient-related outcomes are comparable between IPC with intermittent drainage, and intercostal drainage with pleurodesis. Further, patients managed with an IPC appear to spend less time in hospital, and are less likely to require a subsequent pleural procedure [7,8].The evidence for the use of IPCs is increasingly growing, and the ASAP trial, concluded that "aggressive" daily drainage significantly increased the rate of autopleurodesis, as compared to alternative day drainage, (47 vs. 24%, p = 0.003) as well as decreased the median time to autopleurodesis (54 vs. 90 days) in patients [9]. QoL and patient satisfaction were similar between the groups; however importantly, all cases with nonexpendable lung were excluded from this study [9].…”
mentioning
confidence: 99%